Rope language - Guilfoyle, Johanna, author; Plastini, Johnny, advisor; Lajarin-Encina, Aitor, committee member; Romagni, Domenica, committee member; Moseman, Eleanor, committee member (Colorado State University. Libraries, 2021)
With blistered hands and rope-burned ankles gripping the rope, I look up towards the peeling tape marking the daunting height of 15 feet. I loop the rough fibers over my right foot before clamping it in place with my left. My feet hold steady and I stand up to reach my arms further upwards. I unwrap the rope from my feet and lift them higher before re-looping the rope over my right shoe, again and again, literally sculpting my body, my muscle, my flesh. Through the rope and this repetitive task, I build my flesh. The rope and other symbols of my past are imprinted over and over again. Similarly, the layering and fusing of prints transform inanimate material into bodily experience--I create flesh from repetition, and through this flesh convey the physical narratives contained within. The color and texture of each print builds to create the final collective mass. If any one of the prints were missing, any piece of the narrative, the final piece would exist as a different form. The layered narrative of my work is embedded in encaustic mortality. The amalgam of my life is embedded into flesh. The corporeal experience of my work entices the viewer to become increasingly aware of their own flesh and the narratives contained within.
Keywords: language; abject; printmaking